Developing a manufacturing process to deliver a cost effective and stable liquid human rotavirus vaccine. Issue 15 (8th April 2021) - Hamidi, Ahd; Hoeksema, Femke; Velthof, Pim; Lemckert, Angelique; Gillissen, Gert; Luitjens, Alfred; Bines, Julie E.; Pullagurla, Swathi R.; Kumar, Prashant; Volkin, David B.; Joshi, Sangeeta B.; Havenga, Menzo; et al.
Highlights: A low-cost manufacturing process for a neonatal rotavirus vaccine was developed. The formulation process developed resulted in a stable liquid vaccine at 2–8 °C. No pretreatment of vaccinees with antacid needed before oral administration. Tech. transfer package includes manufacturing, formulation, assays and COGs model. Abstract: Despite solid evidence of the success of rotavirus vaccines in saving children from fatal gastroenteritis, more than 82 million infants worldwide still lack access to a rotavirus vaccine. The main barriers to global rotavirus vaccine coverage include cost, manufacturing capacity and suboptimal efficacy in low- and lower-middle income countries. One vaccine candidate with the potential to address the latter is based on the novel, naturally attenuated RV3 strain of rotavirus, RV3-BB vaccine administered in a birth dose strategy had a vaccine efficacy against severe rotavirus gastroenteritis of 94% at 12 months of age in infants in Indonesia. To further develop this vaccine candidate, a well-documented and low-cost manufacturing process is required. A target fully loaded cost of goods (COGs) of ≤3.50 per course of three doses was set based on predicted market requirements. COGs modelling was leveraged to develop a process using Vero cells in cell factories reaching high titers, reducing or replacing expensive reagents and shortening process time to maximise output. Stable candidate liquid formulations were developed allowing two-year storage at 2–8 °C. In addition, the formulation potentially renders needless the pretreatment of vaccinees with antacid to ensure adequate gastric acid neutralization for routine oral vaccination. As a result, the formulation allows small volume dosing and reduction of supply chain costs. A dose ranging study is currently underway in Malawi that will inform the final clinical dose required. At a clinical dose of ≤6.3 log10 FFU, the COGs target of ≤3.50 per three dose course was met. At a clinical dose of 6.5 log10 FFU, the final manufacturing process resulted in a COGs that is substantially lower than the current average market price, 2.44 USD per dose. The manufacturing and formulation processes were transferred to BioFarma in Indonesia to enable future RV3-BB vaccine production.